Aportes del método de los "puntos pivote" a un estudio prospectivo de seguridad en el campo de la interoperabilidad ferroviaria - Cecília De La Garza (Universidade do Porto, 2005)
In a European project, a study of 25 critical events was conducted in order to show how an accident analysis method could contribute to the safe design of a future organisation. These events are "inter-operable" because they involved a foreign driver or a foreign locomotive in a French border zone. The "pivotal-point" method, used here, requires four steps that connect the work activity analysis, the accident report analysis and the cognitive analysis of the actions and diagnostics, in interaction with the work environment. So, it is possible to explain how incidents occurred and to establish a typology. Four kinds of inter-operable incidents highlighted that the difficulties are linked to communication in a foreign language; the communication and the interaction with the signalling system; and the coordination of the actions and decision-making between various actors of a complex network (the marshalling yard personnel and the drivers). To conclude, some recommendations are given for the design of a safe future organisation taking into account the risks and difficulties identified here. In fact, beyond the technical barriers and safety regulations, real organisational barriers should be considered to guarantee the human reliability and the performance of the socio-technical system.